Failure characterisation in polymer matrix composite for un-notched and notched (open-hole) specimens under tension condition - T. Arifin, A. M.; Abdullah, S.; ., Md. Rafiquzzaman; Zulkifli, R.; Wahab, D. A. (Springer International Publishing, 2014)
his paper presents an investigation of the influences causing failure in the materials comprising polymer matrix composites. Structures with differences in stacking sequences and design configuration are analysed. The objective of this study is to investigate and evaluate the reasons for the failure of composite lamination structures in terms of stress, strength, strain, and Young modulus within a morphology observation of composite materials. The materials selected for the study were a chopped strand mat (CSM) and a woven roving (WR) fabric. These materials are used as reinforcement and are produced by the hand lay-up technique using epoxy and polyester matrix resin. The experiment was performed using specimens made of notched (open-hole; OH) tension and un-notched (UN) shapes. The characteristics of different shapes, materials, and lamination structures are studied in this research. The results showed the failure phenomenon in the structure of the polymer matrix composite is dependent on the characteristics of the material used and the design configuration of both structures.